The monster in the wardrobe - Shipton,Paul; Smedley, Chris (London Oxford University press, 2005)
Luke sat up in bed. 'What's the matter now?' asked his sister Carolyn. Luke was mad about monsters. He was always scaring himself with creepy stories. Tonight was different. Luke pointed to the foot of his bed. A noise was coming from his wardrobe